Considering the Budyko’s Assumption to Estimate Evapotranspiration from Irrigation Districts in China - LIN Yifan; HUO Zailin; WANG Chaozi; ZHANG Chenglong; HAN Zhenzhong; CUI Jing (Guan'gai paishui xuebao, 2022)
【Objective】 The Budyko’s assumption is that evapotranspiration is limited by water in semi-arid regions and by energy in wet regions. This paper applied it to estimate evapotranspiration from irrigated agricultural lands in China. 【Method】 The results calculated using the Budyko equation were tested against irrigation, precipitation, groundwater evaporation and real evapotranspiration measured from 2010 to 2017 from 282 irrigation districts across China. Based on these data and results, we analyzed the accuracy of the Budyko equation for cropped lands under different climatic conditions. 【Result】 The Budyko equation and the Fu's equation, both considering irrigation and groundwater evaporation, are adequate to estimate evapotranspiration from irrigated cropped lands. The mean relative error between the estimated ET and the measured ET is less than 21.7%. Overall, the estimated ET is more accurate for humid areas, where the planting structure and irrigation are less prone to fluctuation and change, than for other areas. Impacted by meteorology, water supply and distribution, soil texture and planting structure in irrigation districts, the parameter ω in the Budyko curves varies spatially and increases, in general, with humidity. 【Conclusion】 The Budyko equation works well for estimating annual evapotranspiration from irrigated cropped lands in China.